An improved mosquito electrocuting trap that safely reproduces epidemiologically relevant metrics of mosquito human-feeding behaviours as determined by human landing catch. (December 2016) - Govella, Nicodem; Maliti, Deodatus; Mlwale, Amos; Masallu, John; Mirzai, Nosrat; Johnson, Paul; Ferguson, Heather; Killeen, Gerry
Abstract Background Reliable quantification of mosquito host—seeking behaviours is required to determine the efficacy of vector control methods. For malaria, the gold standard approach remains the risky human landing catch (HLC). Here compare the performance of an improved prototype of the mosquito electrocuting grid trap (MET) as a safer alternative with HLC for measuring malaria vector behaviour in Dar es Salaam, Tanzania. Methods Mosquito trapping was conducted at three sites within Dar es Salaam representing a range of urbanicity over a 7-month period (December 2012–July 2013, 168 sampling nights). At each site, sampling was conducted in a block of four houses, with two houses being allocated to HLC and the other to MET on each night of study. Sampling was conducted both indoors and outdoors (from 19:00 to 06:00 each night) at all houses, with trapping method (HLC and MET) being exchanged between pairs of houses at each site using a crossover design. Results The MET caught significantly moreAnopheles gambiae sensu lato than the HLC, both indoors (RR [95 % confidence interval (CI)]) = 1.47 [1.23–1.76], P < 0.0001 and outdoors = 1.38 [1.14–1.67], P < 0.0001). The sensitivity of MET compared with HLC did not detectably change over the course of night for eitherAn. gambiae s.l. (OR [CI]) = 1.01 [0.94–1.02], P = 0.27) orCulex spp. (OR [CI]) = 0.99 [0.99–1.0], P = 0.17) indoors and declined only slightly outdoors:An. gambiae s.l. (OR [CI]) = 0.92 [0.86–0.99], P = 0.04), andCulex spp. (OR [CI]) = 0.99 [0.98–0.99], P = 0.03). MET-based estimates of the proportions of mosquitoes caught indoors (P i ) or during sleeping hours (P fl ), as well as the proportion of human exposure to bites that would otherwise occurs indoors (πi ), were statistically indistinguishable from those based on HLC forAn. gambiae s.l. (P = 0.43, 0.07 and 0.48, respectively) andCulex spp. (P = 0.76, 0.24 and 0.55, respectively). Conclusions This improved MET prototype is highly sensitive tool that accurately quantifies epidemiologically-relevant metrics of mosquito biting densities, behaviours and human exposure distribution.